Influence of Cryopreservation by Vitrification on Morphology and Localization of Meiotic Division Spindle of Human Oocytes - Buderatska, Natalia O.; Gontar, Yuliia V.; Lavrynenko, Sergii V.; Ilyin, Igor Ye.; Parnytska, Olga I.; Ilyina, Kateryna I.; Kapustin, Eduard V. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):185.